The Risk of Cervical Cancer in Women Among Han, Bai, Dai and Hani Ethnic Minorities in Yunnan Province of China - Zhao M; Gao MZ; Gu RY; Luo L; Ding SR; He L; Jia Y; Zhang HP; Yang HY; Li GF (Dove Medical Press, 2024)
Min Zhao,1,* Ming-Zhu Gao,1,* Rong-yan Gu,1,* Lei Luo,1 Song-rui Ding,1 Liang He,2 Yue Jia,3 Hong-ping Zhang,3 Hong-ying Yang,3 Gao-feng Li1 1Medical Administration Department, The Third Affiliated Hospital of Kunming Medical University (Yunnan Cancer Hospital, Yunnan Cancer Center), Kunming, Yunnan, People's Republic of China; 2Medical Laboratory Department, The Third Affiliated Hospital of Kunming Medical University (Yunnan Cancer Hospital, Yunnan Cancer Center), Kunming, Yunnan, People's Republic of China; 3Gynecological Department, The Third Affiliated Hospital of Kunming Medical University (Yunnan Cancer Hospital, Yunnan Cancer Center), Kunming, Yunnan, People's Republic of China*These authors contributed equally to this workCorrespondence: Hong-ying Yang; Gao-feng Li, Email yanghy913@126.com; ligaofenghl@126.comBackground: Research on the risk factors for cervical cancer in Yunnan Province's four characteristic ethnic groups (Han, Bai, Dai, and Hani) is lacking.Objective: To study the risk factors of cervical cancer in four ethnic women in Yunnan Province, and to provide evidence for its prevention.Methods: The cervical cancer patients of Han, Bai, Dai and Hani ethnic groups in Yunnan Province who were first diagnosed in the Third Affiliated Hospital of Kunming Medical University (Yunnan Cancer Hospital, Yunnan Cancer Center) from January 2011 to December 2020 were selected as the research objects. The 1:1 matched case-control study method was used, and single factor and conditional logistic regression were used for statistical analysis.Results: HPV types 16, 18 and 58 are mostly related with cervical cancer, the younger the age of the last pregnancy, the more times of pregnancy, childbirth and abortion, especially the younger the first marriage age of Bai and Dai, are the risk factors of cervical cancer; the infection of genital tract bacteria, mycoplasma and chlamydia is closely related to the incidence of cervical cancer in four ethnicities. Multifactorial analysis showed that demographic characteristics and environment/behavior were not included in the influencing factors of cervical cancer; among Han, Bai, Dai and Hani ethnic minorities, contraception (OR=0.29, OR=0.03, OR=0.09, OR=0.16, P< 0.05) was positive factor, HPV infection (OR=64.77, OR=128.71, OR=71.89, OR=40.07, P< 0.01) was a causative factor of cervical cancer.Conclusion: Risk of high parity with cervical cancer could be due to a complex interplay of factors, it is very important to formulate prevention strategies and measures in line with the cervical cancer of Han, Bai, Dai and Hani ethnic groups women in Yunnan Province.Keywords: cervical cancer, risk factors, case-control study, Han, Bai, Dai and Hani ethnic minorities, Yunnan Province